# How do you solve 2( 3x + 4) = 5( x - 5) + 1?

Jun 14, 2017

To solve this equation, you must isolate $x$ through PEMDAS.

#### Explanation:

First, distribute the $2$ to $\left(3 x + 4\right)$, giving you $\left(6 x + 8\right)$ on the left side.

On the right side, distribute the $5$ to the $\left(x - 5\right)$, giving you $\left(5 x - 25\right) + 1$ on the right side.

You should now have

$6 x + 8 = 5 x - 25 + 1$

Add the $+ 1$ to $- 25$, giving you $- 24$.

You should now have

$6 x + 8 = 5 x - 24$

Subtract $5 x$ from both sides to get $x$ on the same side of the equation. You should get

$x + 8 = - 24$

Subtract $8$ from both sides to isolate $x$, leaving you with

$x = - 32$

Hope this helped!

Jun 14, 2017

color(blue)(x=-32

#### Explanation:

$2 \left(3 x + 4\right) = 5 \left(x - 5\right) + 1$

$\therefore 6 x + 8 = 5 x - 25 + 1$

$\therefore 6 x - 5 x = - 25 + 1 - 8$

$\therefore x = - 24 - 8$

:.color(blue)(x=-32

Substitute color(blue)(x=-32

$\therefore 2 \left(3 \left(\textcolor{b l u e}{- 32}\right) + 4\right) = 5 \left(\left(\textcolor{b l u e}{- 32}\right) - 5\right) + 1$

$\therefore 2 \left(- 96 + 4\right) = 5 \left(- 37\right) + 1$

$\therefore - 192 + 8 = - 185 + 1$

$\therefore - 184 = - 184$